2018
DOI: 10.1159/000492549
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activation of β-Catenin in Differentiated Osteoclasts Induces Bone Loss in Mice

Abstract: Background/Aims: Activation of the Wnt/β-catenin signalling pathway has been widely investigated in bone biology and shown to promote bone formation. However, its specific effects on osteoclast differentiation have not been fully elucidated. Our study aimed to identify the role of β-catenin in osteoclastogenesis and bone homeostasis. Methods: In the present study, exon 3 in the β-catenin gene (Ctnnb1) allele encoding phosphorylation target serine/threonine residues was flanked by floxP sequences. We generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
(75 reference statements)
0
14
0
Order By: Relevance
“…While there is strong evidence supporting a role for OBdependent canonical Wnt signaling in the regulation of bone formation and bone resorption, the exact mechanisms by which this pathway affects bone mass via a cell-autonomous effect in OCs remain puzzling. Thus, in OCs, it has been shown that while canonical Wnt β-catenin cascade activation suppresses OCgenesis, noncanonical Wnt/Ror2/Jnk signaling activation favors it (23,(26)(27)(28)(29). Because Sfrp4 acts as a Wnt ligand decoy receptor, its function in skeletal homeostasis is related to regulation of distinct Wnt signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is strong evidence supporting a role for OBdependent canonical Wnt signaling in the regulation of bone formation and bone resorption, the exact mechanisms by which this pathway affects bone mass via a cell-autonomous effect in OCs remain puzzling. Thus, in OCs, it has been shown that while canonical Wnt β-catenin cascade activation suppresses OCgenesis, noncanonical Wnt/Ror2/Jnk signaling activation favors it (23,(26)(27)(28)(29). Because Sfrp4 acts as a Wnt ligand decoy receptor, its function in skeletal homeostasis is related to regulation of distinct Wnt signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Wei et al (26) have reported that while β-catenin activation favors OC proliferation of early precursor cells, its signal must be suppressed to have mature OCs. However, to complicate matters, it has been recently reported that expression of constitutively active β-catenin in OCs in vivo leads to increased OCgenesis (27). On the other hand, several pieces of evidence indicate that noncanonical Wnt signaling activation favors OCgenesis (28)(29)(30).…”
Section: Significancementioning
confidence: 99%
“…The biphasic regulatory effect of the Wnt ligand Wnt3a on osteoclastogenesis is dependent on β-catenin. Wnt3a enhances the proliferation of osteoclast precursors through the activation of β-catenin and impairs the differentiation of osteoclast precursors due to β-catenin constitutive activation ( Sui et al, 2018 ). Besides, the stimulation of OPG in osteoblasts can also block osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although current studies have also focused on the direct modulatory role of Wnt signaling in osteoclast differentiation, the results remain contradictory. Constitutively active β-catenin in osteoclast precursors barely forms osteoclasts, whereas the β-catenin signal is required for the proliferation of osteoclast precursors ( Sui et al, 2018 ). Furthermore, Wnt5a has been shown to activate the Ror2-JNK signaling and enhance RANKL-induced osteoclastogenesis ( Maeda et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the reduction of Lrp5 in the early osteoclast lineage reduced trabecular bone mass, whereas its disruption in late osteoclast precursors did not alter the skeletal phenotype [ 22 ]. By contrast, the constitutive activation of β-catenin is reported to promote osteoclast formation, resulting in bone loss [ 23 ]. To the best of our knowledge, little is known about the role of Wnt-activated osteoclasts in the bone-tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%